Register Used by Basketball Commentators in National Basketball Association : a Comparative Study - Muhammad Haris Zidan; Lina Purwaning Hartanti (SM Institute, 2026)
Sports commentary is a form of spontaneous discourse in which commentators narrate game events while evaluating and interpreting actions in real time. Despite the growing interest in sports discourse, studies on the stylistic register of National Basketball Association (NBA) commentary remain limited. This study aims to identify the types of stylistic registers used by Kevin Harlan and Mike Breen and to analyze their communicative functions in NBA live broadcasts. This research employed a descriptive qualitative design with a comparative approach. The data consisted of 30 utterances (15 from each commentator) collected from authentic NBA broadcast clips uploaded on the 23firey YouTube channel. The data were analyzed using Martin Joos' (1962) Stylistic Register Theory and Judy Delin's (2000) communicative functions framework, following the interactive analysis model of Miles, Huberman, and Saldaña (2018). The findings reveal three stylistic registers: Frozen, Formal, and Casual. Casual Register was dominant in Kevin Harlan's commentary, while Formal Register predominated in Mike Breen's. Frozen Register appeared only in Mike Breen's signature expression, Bang!. The communicative functions identified were Narrating, Evaluating, Elaborating, and Summarizing. Overall, the study demonstrates that stylistic register variation reflects both the communicative demands of live NBA broadcasting and the commentators' individual broadcasting styles.